Achieving drinking water compliance levels for metaldehyde with an acclimated sand bioreactor - Rolph, Catherine A.; Jefferson, Bruce; Brookes, Adam; Hassard, Francis; Villa, Raffaella (Elsevier, 2020)
Metaldehyde removal was delivered to below the 0.1 µg L-1 regulatory concentration in a laboratory scale continuous upflow fluidised sand bioreactor that had undergone acclimation through selective enrichment for metaldehyde degradation. This is the first reported case of successful continuous flow biological treatment of metaldehyde from real drinking water sources treating environmentally realistic metaldehyde concentrations. The impact of the acclimation process was impermanent, with the duration of effective treatment directly related to the elevated concentration of metaldehyde used during the enrichment process. The efficacy of the approach was demonstrated in continuous flow columns at both laboratory and pilot scale enabling degradation rates of between 0.1 and 0.2 mg L-1 h-1. Future work needs to focus on optimisation of the sand bioreactor and the acclimation process to ensure viability and feasibility of the approach at full scale
Keywords: Pesticides; Selective enrichment; Acclimation; Micropollutant removal; Upflow fluidised sand bioreactor